Novel 5-HT6R modulators as mTOR-dependent neuronal autophagy inductors - José Miguel Alcaíno; Gonzalo Vera; Gonzalo Almarza; Carlos F. Lagos; Claudio A. Terraza; Andrea del Campo; Gonzalo Recabarren-Gajardo (Scientific Reports)
Abstract Autophagy is a natural process in which the cell degrades substances through the lysosomal pathway. One of the most studied mechanisms for regulating autophagy is the mTOR signaling pathway. Recent research has shown that the 5-HT6 receptor is linked to the mTOR pathway and can affect cognition in various neurodevelopmental models. Therefore, developing 5-HT6 receptor antagonists could improve cognition by inducing autophagy through the inhibition of the mTOR pathway. Our study reports two in-house-designed 5-HT6R antagonists, PUC-10 and its indazole analogue PUC-55, that induce mTOR-dependent autophagy. PUC-10, an indole-based 5-HT6 receptor antagonist with high binding affinity (Ki = 14.6 nM) and antagonist potency (IC50 = 32 nM), demonstrated more than 90% at 25 µM cellular viability and a high capacity to induce autophagy in the neuroblastoma SH-SY5Y cell line. Similarly, its indazole analogue, PUC-55 (Ki = 37.5 nM), exhibited high cellular viability and potent autophagy-inducing activity. Both compounds induced overexpression of the 5-HT6 receptor after 24 h of stimulation, contrasting with the effects observed with Rapamycin (100 nM), a well-known mTOR inhibitor. Additionally, the signaling pathway was characterized, showing that both PUC-10 and PUC-55 induce autophagy by inhibiting the mTOR pathway, suggesting their potential therapeutic applications for neurological disorders.